Effect of Ti content on spinodal decomposed microstructure and properties of AlCoCrFeNiTix high-entropy alloy coatings prepared by laser cladding - Kun Yue; Xiaoqin Yang; Lin Wang; Liji Su; Quan Xu; Zhe Xu; Chunlong Cheng; Yeqing Wang; Zhijun Wang; Zheng Chen (Journal of Materials Research and Technology)
To enhance the hardness and wear resistance of Q235 substrate, an AlCoCrFeNi high-entropy alloy (HEA) coating was deposited onto the substrate surfaces by laser cladding. However, the performance of the AlCoCrFeNi HEA coating did not meet the desired requirements. Consequently, AlCoCrFeNiTix (x = 0, 0.25, 0.5, 0.75, and 1) HEA coatings were prepared by laser cladding to further improve the coating hardness and wear resistance. The influence of Ti content on the microstructure, hardness, and wear resistance of the coatings was studied. The results showed that Ti promoted the formation of a body-centered cubic (B2) phase, transforming the coating structure into a typical dendritic (DR)–inter-dendritic (ID) structure. The AlCoCrFeNiTi0.25 coating consisted of BCC1 phase and B2 phases. As the Ti content increases, Laves phases emerged in AlCoCrFeNiTix HEA coatings. Spinodal decomposition led to pronounced phase separation in the coating, with elongated nanoparticles of the BCC1 phase precipitating in the DR region and round block-like nanoparticles of the B2 phase precipitating in the ID region. The B2 and Laves phases strengthened the coatings and improved their hardness and wear resistance. The hardness of AlCoCrFeNiTi1 coating reached 828.35 HV0.1, which was 56.29 times higher than that of the AlCoCrFeNi coating, while its wear resistance was 80.7 times greater. Therefore, the addition of Ti effectively improved the hardness and wear resistance of the AlCoCrFeNi HEA coating.